2020
DOI: 10.18203/2349-3933.ijam20201614
|View full text |Cite
|
Sign up to set email alerts
|

A ten year review of depot medroxyprogesterone acetate contraceptive use at Rivers State University Teaching Hospital, South Nigeria

Abstract: Background: Depo Medroxyprogesterone Acetate (DMPA) also known as Depo provera is a long acting progestogen-only contraceptive injection used by women worldwide. It is given deep intramuscularly at interval of 3 months. It is easy to use, effective, safe, convenient and reversible. Objective was to determine the prevalence of DMPA contraceptive method and profile of its acceptors at the RSUTH.Methods: This was a retrospective study of 271 clients attending family planning clinic at the RSUTH from 1st January, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…1,15 They are also unlikely to be married and would benefit from abstinence or barrier methods to prevent sexually transmitted infections (STIs) as well as the contraception effects. 8 Most of the clients that accepted DMPA were multipara which is in keeping with previous studies. 4,9,10,16 This is because it is usually the multiparous women who seek for contraception to limit the family size and space the childbirths.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…1,15 They are also unlikely to be married and would benefit from abstinence or barrier methods to prevent sexually transmitted infections (STIs) as well as the contraception effects. 8 Most of the clients that accepted DMPA were multipara which is in keeping with previous studies. 4,9,10,16 This is because it is usually the multiparous women who seek for contraception to limit the family size and space the childbirths.…”
Section: Discussionsupporting
confidence: 87%
“…Several studies have confirmed the fact that contraception is more readily accepted and used by educated women. 2,8,14 It is important to state that more than 60% of the clients had no side effects indicating a good safety profile of the contraceptive. Menstrual disorders were the commonest complications experienced by the clients with most of them having secondary amenorrhoea and irregular vaginal bleeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation